Legal Analysis of the Advancement of AI and Blockchain Amid Lagging Digital Copyright Regulation in Indonesia - Jubaidi, Didi; Khoirunnisa, Khoirunisa (Universitas Internasional Batam, 2025)
The rapid advancement of Artificial Intelligence (AI) and blockchain technology has reshaped the digital landscape, particularly in content creation, storage, and distribution. Despite these innovations, Indonesia’s copyright law has not kept pace, creating a pressing research problem: the adequacy of existing regulations in addressing AI- and blockchain-based works. This study aims to examine the legal implications of these technologies and evaluate whether Indonesia’s current copyright framework, particularly Law No. 28 of 2014, can effectively respond to such challenges. Using a normative juridical methodology that combines statutory, conceptual, and comparative approaches, the research examines Indonesian copyright law and contrasts it with developments in the European Union and the United States. The findings reveal critical regulatory gaps, including the absence of recognition for non-human authorship, insufficient mechanisms for decentralized content management, and the lack of clarity on smart contract-based licensing. These deficiencies create legal uncertainty that risks weakening the protection of creators’ rights in the digital era. The study contributes by emphasizing the significance of adaptive and technology-responsive reforms, recommending proactive legislative updates and the adoption of flexible legal doctrines to ensure Indonesian copyright law remains effective and relevant in the face of rapid technological change.